Implementation of Hadoop Distributed File System Services in an Application - Anto, Shincy; Anila Ramesh, K; Dias, Ladlie; Sabna, AB (International Journal of Computer Sciences and Engineering, 2025)
Cloud is the collection of computers on the internet that is being offered as a revolutionary storage method for files and Big Data is an evolving term that describes any voluminous amount of structured, semi-structured and unstructured data that has the potential to be mined for information. In our proposed system, we implement a safe method to save Big Data files using Apache Hadoop technology. And here we provide two web services: uploading and downloading of files. Once we upload the files, they are stored in different nodes across the cluster after partitioning. We make the data highly available, by keeping the different copies of data in several nodes. The uploaded files can be retrieved at any time according to our needs. Even if there is a failure at any node, the copy of data on some other nodes makes our system fault tolerant and reliable. Along with that, we can also make our files public or private and thus providing file sharing facility. We offer a security system for storing and managing Big Data files